A brief review on hardware structure of AC electric spring - Jyoti Rokde; Archana Thosar (Institute of Advanced Engineering and Science, 2022)
Decarbonizing power generation and reducing greenhouse gas emissions require renewable energy sources. Intermittent nature of renewable energy sources can cause blackouts, fluctuation in voltage, grid-connected inverter usage, inability to predict power generation, fluctuations in voltage and frequency. It is possible to balance between the supply and demand of power to overcome these problems by using an electric spring (ES). It is necessary to study its work, types, and controlling actions for realizing the benefits of the electric spring. This paper reviews the hardware structure of an ES based on voltage-source inverter (VSI) and current-source inverter (CSI) topologies, in single-phase and three-phase AC power distribution systems with renewable energy sources. The structure, control strategies, operating modes, advantages and disadvantages of each ES topology are elaborated to make it a suitable alternative for resolving different power quality issues caused due to the high penetration of renewable energy sources.